Transformation Routes of PV‐ and PIII‐N‐Substituted Acyclic Diaminocarbenes. Issue 11 (12th December 2018) - Marchenko, Anatoliy; Koidan, Georgyi; Hurieva, Anastasiya; Vlasenko, Yurii; Rozhenko, Alexander B.; Sotiropoulos, Jean‐Marc; Kostyuk, Aleksandr
Abstract : Herein we report on the synthesis of a set of transient N ‐(P III )‐phosphanyl and N ‐(P V )‐phosphoroselenoyl acyclic diaminocarbenes by deprotonation of the corresponding formamidinium salts. It is shown that N ‐(P V )‐substituted acyclic diaminocarbenes undergo 1, 2‐phosphorus shift. Transformations of N ‐(P III )‐substituted acyclic diaminocarbenes result in tetrahydroquinazolines as final products. The proposed mechanism includes the isomerization of the carbenes into transient azomethine ylides followed by their cyclization via electrophilic aromatic substitution. Introduction of the electron‐donating dimetylamino group into the phenyl substituent markedly enhances the rate of the reaction and the yield of the final product. In the case of the morpholine derivative, the corresponding azomethine ylide undergoes opening the morpholine ring giving vinyloxazolidin‐2‐amine. The results are corroborated by DFT calculations. Abstract : In the absence of a trapping agent P III ‐ N ‐substituted acyclic diaminocarbenes prepared by deprotonation of the corresponding salts isomerize into transient azomethine ylides followed by electrophilic aromatic substitution to afford tetrahydroquinazolines. P V ‐ N ‐substituted acyclic diaminocarbenes undergo 1, 2‐phosphorus shift resulting in phosphane selenides.